Heat‐labile Escherichia coli toxin enhances the induction of allergen‐specific IgG antibodies in epicutaneous patch vaccination. Issue 1 (30th September 2016) - Cabauatan, C. R.; Campana, R.; Niespodziana, K.; Reinisch, C.; Lundberg, U.; Meinke, A.; Henning, R.; Neubauer, A.; Valenta, R.
Abstract: Epicutaneous allergen‐specific immunotherapy (EPIT) is proposed as an alternative route for allergen‐specific immunotherapy (AIT). The induction of allergen‐specific blocking IgG antibodies represents an important mechanism underlying AIT, but has not been investigated for EPIT. Here, we compared the induction of allergen‐specific blocking IgG in outbred guinea pigs which had been immunized with recombinant birch pollen allergen Bet v 1 using patch delivery system (PDS) with or without heat‐labile toxin (LT) from Escherichia coli or subcutaneously with aluminum hydroxide (Alum)‐adsorbed rBet v 1. Only subcutaneous immunization with Alum‐adsorbed rBet v 1 and epicutaneous administration of rBet v 1 with PDS in combination with LT from E. coli induced allergen‐specific IgG antibodies blocking allergic patients' IgE, but not immunization with rBet v 1 via PDS alone. Our results suggest that patch vaccination with rBet v 1 in combination with LT may be a promising strategy for allergen‐specific immunotherapy against birch pollen allergy.